Analysis of alternative energy sources - Kuzmin, K. S. (ТДАТУ, 2020)
For the rational use of natural resources and the transition to sustainable development of the regional economy, it is necessary to carry out the introduction of new engineering designs, to rationally use the natural resources; to control the usage of flora objects.
Keywords: alternative energy sources; ecology; rational use of natural resources